Beaufort Gyre Liquid Freshwater Content Change Under Greenhouse Warming From an Eddy‐Resolving Climate Simulation - Xuan Shan; Michael Spall; Shantong Sun; Lixin Wu (Geophysical Research Letters)
Abstract Future changes in the Beaufort Gyre liquid freshwater content (LFWC) are important for the local and global climate. However, traditional climate models cannot resolve oceanic and atmospheric eddies that are critical to the LFWC variations. In this study, we investigate physical processes controlling Beaufort Gyre LFWC changes in an eddy‐resolving simulation. The model simulation largely reproduces the observed LFWC changes, and projects a long‐term LFWC increase with an intensification of its decadal variability during the 21st century. Freshwater budget analysis suggests that future LFWC changes are strongly influenced by sea ice melt. The conversion from solid to liquid phase provides more liquid freshwater into the ocean. Meanwhile, sea ice loss enhances the efficiency of air‐sea momentum transfer, leading to increased wind‐driven freshwater convergence and its variability. The decadal variation of the LFWC will regulate Arctic freshwater exports and coincident with an O (0.5 Sv) change in the meridional overturning circulation.